Study on the Vibroimpact Response of the Particle Elastic Impact on the Metal Plate - Yang Yang; Lirong Wan (Shock and Vibration)
In order to study the contact and vibration response in the reciprocating impact between coal gangue particles and metal plate, on the basis of the Hertz contact theory, L-N contact model, and the Lagrange equation, this paper established an impact-contact model when the particles free falling to vertically impacts on the metal plate. The variable damping simulation method is proposed, and the accuracy of the variable damping simulation in the medium reciprocating collision is verified by combining the constant damping simulation, the variable damping simulation, and the falling body impact-contact model. The functional relationship between the damping term and the initial impact velocity in Adams simulation is also obtained. Then, through the rigid-flexible coupling method which is combined by Adams and Hypermesh, the three types of variable damping simulations are conducted: the simulation that the free-falling rigid rock sphere impact on the rigid metal plate, the simulation that the elastic rock sphere impact on the rigid metal plate, and the simulation that the elastic rock sphere impact on the elastic metal plate, respectively. Furthermore, contact and vibrate responses of the rock sphere and the metal plate in the three types of the simulation are studied. The results show that the impact-contact response of the rock sphere obtained from the simulation that the elastic rock sphere impact on the elastic metal plate is more accurate. After the flexible treatment of the rock sphere and the metal plate, most of the system energy is consumed during the impact. The conclusions will provide a theoretical calculation method for the medium vertical reciprocating impact and a theoretical basis for the setting of the damping term in Adams simulation and support the research basis for the study of the impact behavior between coal gangue particles and the metal plate.